GE_GERICHTE C/11533/2014 vom 6. Mai 2016 - GE Cour de justice (2016)
VALEUR LITIGIEUSE ; SÉQUESTRE(LP) ; GAGE ; ACTION EN REVENDICATION(SAISIE) ; EXTINCTION D'UN DROIT RÉEL ; JOUR DÉTERMINANT ; NANTISSEMENT ; CRÉANCE FUTURE ; BANQUE | LP.109;